1994
DOI: 10.1093/infdis/169.4.801
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Hepatitis E Virus Seroprevalence by Using Recombinant Fusion Proteins and Synthetic Peptides

Abstract: Recombinant antigens from hepatitis E virus (HEV) open-reading frames 2 and 3 were expressed in Escherichia coli as cytidine monophosphate-2-keto-3-deoxyoctulosonic acid synthetase (CKS) fusion proteins, purified, and used to develop an EIA for the detection of antibodies. Serologic results were compared with those of previous assays by testing 102 samples from an HEV outbreak in Somalia. This CKS/HEV EIA detected anti-HEV in all 97 sera found reactive previously and in an additional 2 samples, which were show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
45
0
4

Year Published

1995
1995
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(53 citation statements)
references
References 9 publications
4
45
0
4
Order By: Relevance
“…The seroprevalence of anti-HEV IgG in subjects residing in the Manguinhos area is consistent with previous seroprevalence data reported from non-endemic areas for HEV, ranging from 1 % to 5 % (Dawson et al 1992, Paul et al 1994.…”
Section: Discussionsupporting
confidence: 91%
“…The seroprevalence of anti-HEV IgG in subjects residing in the Manguinhos area is consistent with previous seroprevalence data reported from non-endemic areas for HEV, ranging from 1 % to 5 % (Dawson et al 1992, Paul et al 1994.…”
Section: Discussionsupporting
confidence: 91%
“…In that study, no hepatitis E-seropositive adults were identified among 35 persons tested (RichardLenoble et al 1995). The prevalence of hepatitis E in Tanzania is comparable to other regions of low endemicity, such as Europe and the United States (Paul et al 1994;Zanetti et al 1994;Mast et al 1997).…”
Section: Discussionmentioning
confidence: 94%
“…Hepatitis A (Sorin), C (Abbott) and E antibody (Abbott) (Paul et al 1994) seropositivities were determined by ELISA. Specimens reactive in the hepatitis C or E assays were repeated and considered positive only if repeatedly reactive in duplicate.…”
Section: Viral Hepatitis Assaysmentioning
confidence: 99%
“…The genetic variation of the HEV genome has been demonstrated in different clinical isolates obtained from outbreaks of HEV in several areas (6,14,16). Recombinant antigens representing the putative structural gene sequence derived from open-reading frame (ORF) 2 and ORF3 of the HEV genome have been investigated extensively for the development of a test of recombinant-based enzymelinked immunosorbent assay (ELISA) or a Western blot assay for diagnosis of HEV infection (5,12,15). The newly developed serological diagnostic systems for HEV infection have been widely used to study the seroprevalence among different study populations of epidemic areas (3,9,12,15).…”
mentioning
confidence: 99%
“…Recombinant antigens representing the putative structural gene sequence derived from open-reading frame (ORF) 2 and ORF3 of the HEV genome have been investigated extensively for the development of a test of recombinant-based enzymelinked immunosorbent assay (ELISA) or a Western blot assay for diagnosis of HEV infection (5,12,15). The newly developed serological diagnostic systems for HEV infection have been widely used to study the seroprevalence among different study populations of epidemic areas (3,9,12,15). In order to demonstrate the prevalence of IgG antibodies to HEV (IgG anti-HEV) in Southern Taiwan, we have done a retrospective serological analysis in healthy individuals among different study populations.…”
mentioning
confidence: 99%